The effects of sex-steroids and menstrual cycle/oestrous phases on knee ligament laxity in humans and rodents / Firouzeh Dehghan - Dehghan, Firouzeh (2014)
The incidence of non-contact knee injury was reported higher in female than male. In female, the occurrence of this injury was related to different phases of the menstrual cycle. In view of this, we investigated the followings: (i) changes in knee laxity in rodent model under different sex-steroid influence; (ii) mechanisms underlying changes in knee laxity, which involves differential expression of relaxin receptors and (iii) correlation between knee laxity and serum levels of sex-steroids and relaxin at different phases of the menstrual cycle. In first part of the study, ovariectomized WKY rats were divided into different treatment groups (n=6 per group): different doses of 17 β-oestradiol, progesterone and testosterone were administered. The hormones were injected subcutaneously for 3 consecutive days. In parallel, steroid hormone receptor blockers and enzyme inhibitor (ICI 182780, PHTPP, MPP, Mifepristone, Flutamide, and Finasteride) were also injected with the respective agonist. In parallel, intact rats were grouped based on their oestrous cycle stages: proestrus, estrus, metestrus and diestrus. In ovariectomized steroid treated and intact rats, knee range of motion (ROM) was measured by using a digital miniature goniometer. The rats were sacrificed and expression of relaxin receptor isoforms, RXFP1 and RXFP2 mRNAs and proteins in knee ligaments and tendons were determined. Meanwhile, in humans, changes in knee laxity were observed at different phases of the menstrual cycle in the female athletes. The knee varus and valgus angles were determined at different phases of the menstrual cycle by using an orthopedic goniometer ruler. Blood was withdrawn and serum levels of oestrogen, progesterone and relaxin were determined in human at different phases of their menstrual cycle. Our findings showed a significant increase in knee ROM in rats following oestrogen and progesterone treatment however was decreased following testosterone treatment. Changes in knee ROM was antagonized by the concomitant administration of oestrogen, progesterone and androgen receptor antagonists. Knee ROM was high at proestrus and diestrus stages of the oestrous cycle. Progesterone and oestrogen up-regulated while testosterone down-regulated RXFP1 and RXFP2 mRNA and protein expressions which were antagonized by the respective steroid hormone antagonist. Meanwhile, relaxin administration increases knee ROM in oestrogen and progesterone treated but not testosterone treated groups indicating relaxin receptor up-regulation. In humans, significant difference in knee varus and valgus angles were observed in female athletes and non-athletes at different phases of the menstrual cycle which was the highest in the ovulatory and menstrual phases. Non-athletes have higher medial and lateral knee laxity as compared to athletes. This study has provided an insight into the mechanism underlying sex-steroid control of knee ROM via modulating the expression of RXFP1 and RXFP2 receptors. In rodents, increased RXFP1 and RXFP2 expressions could contribute to increase in knee laxity. In humans, the increase in laxity at ovulatory and mid-luteal phases of the cycle was consistent with high level of oestrogen and progesterone. In both intact rats and humans, strong correlations was noted between knee laxity and serum relaxin levels. Our study has provided the basis underlying female susceptibility towards non-traumatic knee injury at different phases of their reproductive cycle.